Laser printing of certain pixels of graphene nanoribbons - M.S. Komlenok; P.V. Fedotov; P.A. Pivovarov; V.I. Konov (Компьютерная оптика)
A possibility of laser printing of graphene nanoribbon pixels while preserving the integrity of the structure and shape on the silicon substrate in accordance with the irradiated laser spot is demonstrated. To provide the transfer, a target consisting of a transparent sapphire plate and an absorbing thin titanium film (500 nm thick) coated with a film consisting of graphene nanoribbons is irradiated with a KrF excimer laser (λ=248 nm, τ=20 ns). Optimal conditions for laser irradiation are determined and a technique is developed for transferring a carbon nanomaterial from a growth nickel surface to a titanium film aimed at creating stronger bonds between the nanoribbons. Raman spectroscopy confirms the preservation of structural features of the synthesized atomically precise 7-atoms-wide graphene nanoribbons with an armchair edge during laser transfer.